STUDY ON GENETIC VARIATION AND RELATIONSHIPS AMONG FOUR ACACIA SPECIES USING RAPD AND SSCP MARKER - Anthonius Y.P.B.C. Widyatmoko; Atsushi Watanabe; Susumu Shiraishi (Indonesian Journal of Forestry Research, 2010)
Genetic diversity and relationship of four Acacia species, Acacia aulacocarpa, A. Cunn. ex Benth., A. auriculiformis Cunn. ex Benth., A. crassicarpa Cunn. ex Benth. and A. mangium Willd. were investigated using DNA molecular markers. Using RAPD analysis, a total of 20 arbitrar y primers successfully gave 127 polymorphic fragments. These RAPD data were used to estimate genetic distance and construct dendrograms using the unweighted pair-group with the arithmetic mean average (UPGMA) method. The four species were divided into two major clusters. A. auriculiformis and A. mangium were in one cluster, and the other cluster contained both A. aulacocarpa and A. crassicarpa. The divergence time of the two species (A. auriculiformis and A. mangium) in the former cluster appeared to be relatively early in comparison to in the latter (A. aulacocarpa and A. crassicarpa) based on RAPD data. This result was also supported by Principal Component Analysis (PCA). Among the four species, A. aulacocarpa showed the highest divergence in nuclear DNA (ncDNA), followed by A. auriculiformis. SSCP analysis also revealed that these two species possessed a haplotypic variation of the trnL-trnF intergenic spacer region of chloroplast DNA. In A. aulacocarpa, a large difference in the composition of both nuclear and chloroplast genomes was obser ved between populations distributed in Queensland, Australia and those in New Guinea Island. In contrast, compared to the other species, A. mangium showed the lowest genetic diversity and less genetic differentiation among populations.